RANCANG BANGUN MODEL BISNIS EKOWISATA GRASBERG PASCA TAMBANG - Edi Suryanto; Arif Imam Suroso; Rokhani Hasbullah (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Grasberg post mining land of PT Freeport Indonesia (PTFI) has the opportunity to become an attractive ecotourism location. The objectives of this study are (1) Analyze current business models. (2) Analyze internal and external factors that affect the post-mining Grasberg ecotourism business model. (3) Design a verified business model (BMC-1) by considering internal and external analysis. (4) Formulation of strategies and policy priorities for post-mining Grasberg ecotourism development. The research method used was AHP, BMC, PESTEL and VRIO. The results showed that the current business model with several initial indicators for each of the 9 elements of the block model. Internal factors that have a sustainable competitive advantage are location, tourism potential, supporting facilities and facilities, the ability to manage mining tourism, the ability to work in teams, the ability to produce innovation and creativity. External factors that affect the business model, political aspects are influenced by regime change which then affects the share ownership portion as well as cabinet changes as well as the security stability factor. The design of the WTG (Grasberg Mine Tourism) business model resulted in a verified BMC with the addition of indicators for the nine elements of the model. The priority of developing WTG policies focuses on alternative development of tourism services, participation of indigenous peoples, management of activities and coordination of indigenous peoples. The conclusion of this research is to be able to go to the commercial tourism industry, WTG managers need to focus on the key activity elements, the value proposition element, the key resource elements, and the key partner element. Keywords: AHP, BMC, PESTEL, Post Mine Tourism, VRIO